2010
DOI: 10.1177/1947603510392024
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating Blast Injury to the Knee of a United States Soldier Treated with Allograft Mosaicplasty

Abstract: Objective:This is the first report of successful allograft mosaicplasty treatment of a large osteochondral lesion of the knee caused by a blast fragment sustained during combat operations. The patient was able to return to active duty following rehabilitation.Methods:An active-duty infantryman sustained an osteochondral lesion of the medial femoral condyle caused by a metallic fragment of an explosively formed projectile. Initial treatment consisted of removal of the foreign body and primary closure. The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…56 Eichinger et al reported on a soldier who returned to duty after undergoing OCA for an osteochondral defect caused by a penetrating blast injury. 57 These reports of improved outcomes in higher level military personnel are consistent with the data seen in high performing civilian athletes.…”
Section: Summary Of Clinical Evidencesupporting
confidence: 77%
See 1 more Smart Citation
“…56 Eichinger et al reported on a soldier who returned to duty after undergoing OCA for an osteochondral defect caused by a penetrating blast injury. 57 These reports of improved outcomes in higher level military personnel are consistent with the data seen in high performing civilian athletes.…”
Section: Summary Of Clinical Evidencesupporting
confidence: 77%
“…[37][38][39] This is in contrast to when looking at the elite unit activity duty members, who on average had a full return to duty rate within a year, as seen in the studies by Cook et al and Eichinger et al, referenced previously. 56,57 This dichotomy in return to duty rates highlights the difference among military members of various backgrounds, and while outside the scope of this review, a thorough understanding of the impact of nonmusculoskeletal comorbid conditions remains a particularly elusive aspect of many cases.…”
Section: Summary Of Clinical Evidencementioning
confidence: 99%